Tensile Cohesive Laws of Adhesive Joints as a Function of the Adhesive Thickness - R. P. R. O. Antunes; R. D. S. G. Campilho (Technological Innovation in Engineering Research Vol. 3, 2022)
Because of the high level of responsibility that bonded structures carry, it is vital to precisely forecast the fracture behavior under a variety of loads. For strength prediction purposes, numerical simulations, recurring to Cohesive Zone Models (CZM), can be performed. In this work, a numerical analysis is carried out to verify the effect of adhesive thickness (tA) variation on the value of tensile fracture toughness (Gnc) of a bonded joint. The cohesive properties and geometric dimensions introduced as base properties in the simulation program were also experimentally obtained by the direct method. The numerical work consists of replicating the experimental data, namely the load-displacement (P-d) curves, to validate the obtained cohesive laws for the different tested tA. The triangular CZM was selected for this work, recurring to 2D modelling in plane-strain conditions, this being the most appropriate condition for the geometry in question. As a result of this research, CZM rules for the Sikaforce® have been presented and confirmed for the design of bonded structures, greatly speeding up the process.